Teachers’ Capacity Building: A Genuine Mechanism for Achieving Human Capital Development in Nigeria - Adebanjo Adekunle Adetayo; Lucky Amede (Universitas Tanjungpura, 2021)
This study examined teachers’ capacity building as genuine mechanism achieving human capital development in Nigeria. This study adopted the descriptive survey design. Purposive sampling technique was used to select 330 respondents from the secondary schools in Lagos East Senatorial District. The instrument for this study was a researchers-designed questionnaire and it was validated by three Educational experts. The instruments were pilot-tested and Cronbach alpha formula was used to test the reliability of the instrument and the coefficient was 0.81. Three research questions were raised and answered. The results of the findings revealed the extent to which teachers’ capacity building can enhance the achievement of human capital development in Nigeria is very high. The study also indicated several challenges militating against teachers’ capacity building in Nigeria and that the itemized strategies are laudable for improving teachers capacity building in Nigeria. The study, therefore, concluded that extent to which teachers’ capacity building can enhance the achievement of human capital development in Lagos East Senatorial District of Lagos State is high. The study, therefore, recommended that attention should be paid to development programmes that would make teaching career appealing and geared towards achieving human capital development in Nigeria. Government should also device more strategies that will enhance capacity building of teachers’ Educational administrators and policy formulators should implement policies that would surmount the challenges facing teachers’ professional development in Nigeria. Key Words: Education, Human Capacity building, human capital development and economic growth